2023
DOI: 10.3389/frcrb.2023.1241637
|View full text |Cite
|
Sign up to set email alerts
|

Toxicology of carbon nanomaterials in the Caenorhabditis elegans model: current status, characterization, and perspectives for testing harmonization

Francine Côa,
Leandro de Sá Bortolozzo,
Daiana Silva Ávila
et al.

Abstract: Carbon nanomaterials are promising advanced materials for novel technologies. Therefore, biosafety studies are mandatory to support their safe development, uses, and disposal in sustainable innovation. Traditional toxicological assays are typically expensive, time-consuming, and have low throughput; they have been replaced by new approach methodologies (NAMs) focused on in vitro, in chemico and in silico approaches, along with alternative models. Caenorhabditis elegans has emerged as a complete model organism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 109 publications
0
1
0
Order By: Relevance
“…[ 83–99 ] Functionalization can improve the electronic and optical properties of SWCNTs, making them useful in electronics, [ 100 ] photonics, [ 101 ] energy storage, [ 102 ] and agriculture applications, [ 103,104 ] as well as in the biomedical field. [ 105–112 ] Several studies demonstrated the feasibility of SWCNTs as fluorescence sensors or markers in vivo. [ 79–81,113–123 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 83–99 ] Functionalization can improve the electronic and optical properties of SWCNTs, making them useful in electronics, [ 100 ] photonics, [ 101 ] energy storage, [ 102 ] and agriculture applications, [ 103,104 ] as well as in the biomedical field. [ 105–112 ] Several studies demonstrated the feasibility of SWCNTs as fluorescence sensors or markers in vivo. [ 79–81,113–123 ]…”
Section: Introductionmentioning
confidence: 99%